PENGARUH PELATIHAN DAN KOMITMEN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. JINGGA LANGIT MEDIA - Mentari; Vembra Anandita (Jurnal Ekonomi dan Industri, 2020)
To determine the effect of training and work commitment on work productivity at PT. Jingga Langit Media. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Jingga Langit Media. This research sampling technique uses census sampling, where all members of the population are sampled. Training and work commitment have a positive and significant effect on work productivity at PT. Jingga Langit Media, both partially and simultaneous.